Glycemic thresholds for activation of glucose counterregulatory systems are higher than the threshold for symptoms. - Schwartz, N S (1987)
To define glycemic thresholds for activation of glucose counterregulatory systems and for symptoms of hypoglycemia, we measured these during stepped reductions in the plasma glucose concentration (in six 10-mg/dl hourly steps) from 90 to 40 mg/dl under hyperinsulinemic clamp conditions, and compared these with the same measurements during euglycemia (90 mg/dl) under the same conditions over 6 h in 10 normal humans. Arterialized venous plasma glucose concentrations were used to calculate glycemic thresholds of 69 +/- 2 mg/dl for epinephrine secretion, 68 +/- 2 mg/dl for glucagon secretion, 66 +/- 2 mg/dl for growth hormone secretion, and 58 +/- 3 mg/dl for cortisol secretion. In contrast, the glycemic threshold for symptoms was 53 +/- 2 mg/dl, significantly lower than the thresholds for epinephrine (P less than 0.001), glucagon (P less than 0.001), and growth hormone (P less than 0.01) secretion. Thus, the glycemic thresholds for activation of glucose counterregulatory systems during decrements in plasma glucose lie within or just below the physiologic plasma glucose concentration range, and are substantially higher than the threshold for hypoglycemic symptoms in normal humans. These findings provide further support for the concept that glucose counterregulatory systems are involved in the prevention, as well as the correction, of hypoglycemia.